1999
DOI: 10.1159/000026088
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Chromosomal Abnormalities in the Al Jahra Region of Kuwait

Abstract: Objective: One hundred and seventy-seven newborn babies with chromosomal abnormalities were studied at the Al-Jahra satellite clinic of the Kuwait Medical Genetics Centre (KMGC), Kuwait, over a 7-year period from January 1983 to December 1989 to make a reanalysis and recomputation of the statistical results of the previous short-term studies. Methods: The data were collected from the registry of chromosomal abnormalities and from the clinical records of the patients in KMGC retrospectively. Controls were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
2
2
Order By: Relevance
“…Neopterin serum level was found to correlate positively with tumor stage and negatively with prognosis in several malignancies. In addition, it is elevated during transplant rejections, autoimmune diseases and viral infections like hepatitis or HIV [5]. Contrary to our finding that neopterin is significantly elevated only in Sézary patients, Hamerlinck [5]reported that neopterin is not elevated in Sézary but in later-stage MF patients.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Neopterin serum level was found to correlate positively with tumor stage and negatively with prognosis in several malignancies. In addition, it is elevated during transplant rejections, autoimmune diseases and viral infections like hepatitis or HIV [5]. Contrary to our finding that neopterin is significantly elevated only in Sézary patients, Hamerlinck [5]reported that neopterin is not elevated in Sézary but in later-stage MF patients.…”
Section: Discussioncontrasting
confidence: 95%
“…In addition, it is elevated during transplant rejections, autoimmune diseases and viral infections like hepatitis or HIV [5]. Contrary to our finding that neopterin is significantly elevated only in Sézary patients, Hamerlinck [5]reported that neopterin is not elevated in Sézary but in later-stage MF patients. We observed an increase in neopterin levels with the tumor burden in non-leukemic CTCL like MF [7].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The increased incidence of Down syndrome in Dubai is comparable to the reported incidences among Arab nationals from several other regions, namely Kuwait, Saudi Arabia, Qatar, Israel and Libya, which are in the range of 1.93-3.5/1,000 live births ( table 2 ) [9][10][11][12][13][14][15][16][17][18] . The incidence of 3.13/1,000 observed in the UAE population in Dubai is higher than most of the other Arab populations except for Kuwait, where it is reported to be between 2.9 and 3.50/1,000 [9,10] .…”
Section: Discussionsupporting
confidence: 66%
“…The incidence of 3.13/1,000 observed in the UAE population in Dubai is higher than most of the other Arab populations except for Kuwait, where it is reported to be between 2.9 and 3.50/1,000 [9,10] . The mean maternal age (33.48 8 8.08 years, range 17-54 years) in UAE nationals was lower compared to Egypt (38.2 years) and Qatar (35.4 8 6.5 years, range 21-51), but was slightly higher than that of Lebanon (32.19 years) [17][18][19] .…”
Section: Discussionmentioning
confidence: 71%